2015
DOI: 10.1161/circheartfailure.113.000920
|View full text |Cite
|
Sign up to set email alerts
|

Both High and Low HbA1c Predict Incident Heart Failure in Type 2 Diabetes Mellitus

Abstract: Background-Type 2 diabetes mellitus is an independent risk factor for heart failure development, but the relationship between incident heart failure and antecedent glycemia has not been evaluated. Methods and Results-The Genetics of Diabetes Audit and Research in Tayside Study study holds data for 8683 individuals with type 2 diabetes mellitus. Dispensed prescribing, hospital admission data, and echocardiography reports were linked to extract incident heart failure cases from December 1998 to August 2011. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 48 publications
1
33
0
2
Order By: Relevance
“…The findings were in good agreement with many studies that had shown the relationship between overall glycemic level and LV function. Parry et al found that HbA1c >10% was independently correlated with the risk of heart failure (hazard ratio = 1.80, 95% CI: 1.60–2.16). Shi et al identified a correlation between elevated serum HbA1c levels and decreased LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were in good agreement with many studies that had shown the relationship between overall glycemic level and LV function. Parry et al found that HbA1c >10% was independently correlated with the risk of heart failure (hazard ratio = 1.80, 95% CI: 1.60–2.16). Shi et al identified a correlation between elevated serum HbA1c levels and decreased LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiograms are reported by fully accredited sonographers (either British Society of Echocardiography or European Society of Cardiovascular Imaging). This database has been used previously to determine the presence of left ventricular systolic dysfunction …”
Section: Methodsmentioning
confidence: 99%
“…Long‐term measurement of cIMT and TPA may aid the clinicians in the prediction and treatment of severe future events . Multiple studies have been reported that showed the progression of these biomarkers is associated with an elevated risk of stroke or CVD . Hence, in this study, our aim was to predict the 10‐year measurements of carotid image‐based phenotypes by fusing the traditional CV risk biomarkers with current image phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases (CVD) especially heart attack and stroke are the leading causes of deaths around the world with higher incidence rates in males as compared to females . Around 90% of these deaths are attributed to the conventional cardiovascular risk factors such as ethnicity, gender, chronological age, diabetes, smoking, obesity, hyperlipidemia, and hypertension . However, the traditional risk factors do not explain morphological changes in the blood vessels and elevation of coronary artery diseases especially atherosclerosis in every individual …”
Section: Introductionmentioning
confidence: 99%